2017
DOI: 10.4103/0259-1162.183161
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of above knee amputation with combined and modified nerve blocks

Abstract: We report a successful management of a case of methicillin-resistant Staphylococcus aureus positive right lower limb cellulitis for above knee amputation under combined nerve blocks. The ongoing sepsis, thrombocytopenia, and severe respiratory infection with wheeze made us avoid both neuraxial block and general anesthesia and plan for a nerve block. We instituted a modified high inguinal femoral block along with sciatic and lateral femoral nerve blocks separately to successfully conduct the case. We decided to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…In a patient on ECMO requiring lower extremity amputation, the goals of anaesthesia must be weighed against the risk of exacerbating complications such as haemodynamic and respiratory instability. Our report is similar to reports of previous authors where regional anaesthesia was able to be used as a safe and satisfactory alternative anaesthetic technique in a critically ill patient requiring lower limb amputation surgery 12 13. As the duration of the nerve blocks can last for 24 hours, their analgesic effect can reduce immediate postoperative pain, opioid consumption and their related side effects 14 15.…”
Section: Discussionsupporting
confidence: 89%
“…In a patient on ECMO requiring lower extremity amputation, the goals of anaesthesia must be weighed against the risk of exacerbating complications such as haemodynamic and respiratory instability. Our report is similar to reports of previous authors where regional anaesthesia was able to be used as a safe and satisfactory alternative anaesthetic technique in a critically ill patient requiring lower limb amputation surgery 12 13. As the duration of the nerve blocks can last for 24 hours, their analgesic effect can reduce immediate postoperative pain, opioid consumption and their related side effects 14 15.…”
Section: Discussionsupporting
confidence: 89%
“…In a case series published by Baddoo, 10 3 in 1 femoral nerve block and Labat's approach of sciatic nerve block using landmark technique was used for above‐knee amputation but they encountered partial block failure in three cases. Similarly, combined femoral and sciatic nerve block was reported to be effective for above‐knee amputation for right lower limb cellulitis by Kumar et al 11 Akkaya et al 12 also found peripheral nerve blocks to be a safe and effective method with lesser hemodynamic changes compared with spinal anesthesia in patients undergoing total knee arthroplasty.…”
Section: Discussionmentioning
confidence: 94%
“…reported their experience of a successful management of a case of methicillin-resistant Staphylococcus aureus positive right lower limb cellulitis for AKA under combined nerve blocks. [ 9 ] They attributed this success due to use of ultrasound. We successfully conducted US PNB in all five patients, and our experience was very good.…”
Section: Discussionmentioning
confidence: 99%